Risk Factors for Reoperation Following Final Fusion After the Treatment of Early-Onset Scoliosis with Traditional Growing Rods. (7th October 2020) - Du, Jerry Y.; Poe-Kochert, Connie; Thompson, George H.; Hardesty, Christina K.; Pawelek, Jeff B.; Flynn, John M.; Emans, John B.
Abstract : Background: Although there is a high rate of reoperation after final fusion following the treatment of early-onset scoliosis with use of traditional growing rods, the risk factors for reoperation are unknown. The purpose of the present study was to identify risk factors associated with the need for reoperation after final fusion for the treatment of early-onset scoliosis. Methods: A multicenter database for patients with early-onset scoliosis was retrospectively analyzed. Patients managed with traditional growing rods and final fusion were identified (n = 248). The inclusion criteria were ≥1 lengthening procedure with traditional growing rods and ≥2 years of follow-up after final fusion or revision surgery within 2 years after final fusion (167 patients; 67%). Patients requiring reoperation following final fusion were compared with patients who did not require reoperation. The data that were analyzed included demographic characteristics, comorbidities, spinal deformity characteristics, radiographic measurements, perioperative details, and complications during all stages of treatment. A multivariate regression model was used to identify independent risk factors. Results: The mean duration of follow-up from the initial visit to the latest visit was 10.7 ± 4.1 years, and the mean duration of follow-up after final fusion was 4.9 ± 3.1 years. Thirty-two (19%) of the 167 patients required reoperation following final fusion. Curve progression requiring revision surgery during lengthening with traditional growing rods (adjusted odds ratio [aOR], 21.137 per event; p = 0.028), the number of levels spanned with traditional growing rods (aOR, 1.378 per level; p = 0.007), and the duration of treatment with traditional growing rods (aOR, 1.220 per year; p = 0.035) were independently associated with revision surgery after final fusion. Conclusions: Independent risk factors for curve progression requiring reoperation during lengthening with traditional growing rods that require operative intervention include increasing number of levels spanned with traditional growing rods and longer duration of treatment with traditional growing rods. These findings may help with patient counseling and potentially guide surgeon decision-making. Level of Evidence: Prognostic Level IV . See Instructions for Authors for a complete description of levels of evidence.